Procedural sedation and analgesia versus general anesthesia for hysteroscopic myomectomy (PROSECCO trial): A multicenter randomized controlled trial. - Julia F van der Meulen; Marlies Y Bongers; Lisa G van der Zee; Jaklien C Leemans; Ruben G Duijnhoven; Robert A de Leeuw; Lucilla E Overdijk; Celine M Radder; Lucet F van der Voet; Nicol A C Smeets; Huib A A M van Vliet; Wouter J K Hehenkamp; et al. (PLoS Medicine, 2023)
Background Hysteroscopic resection is the first-choice treatment for symptomatic type 0 and 1 fibroids. Traditionally, this was performed under general anesthesia. Over the last decade, surgical procedures are increasingly being performed in an outpatient setting under procedural sedation and analgesia. However, studies evaluating safety and effectiveness of hysteroscopic myomectomy under procedural sedation are lacking. This study aims to investigate whether hysteroscopic myomectomy under procedural sedation and analgesia with propofol is noninferior to hysteroscopic myomectomy under general anesthesia. Methods and findings This was a multicenter, randomized controlled noninferiority trial conducted in 14 university and teaching hospitals in the Netherlands between 2016 and 2021. Inclusion criteria were age ≥18 years, maximum number of 3 type 0 or 1 fibroids, maximum fibroid diameter 3.5 cm, American Society of Anesthesiologists class 1 or 2, and having sufficient knowledge of the Dutch or English language. Women with clotting disorders or with severe anemia (Hb < 5.0 mmol/L) were excluded. Women were randomized using block randomization with variable block sizes of 2, 4, and 6, between hysteroscopic myomectomy under procedural sedation and analgesia (PSA) with propofol or under general anesthesia (GA). Primary outcome was the percentage of complete resections, assessed on transvaginal ultrasonography 6 weeks postoperatively by a sonographer blinded for the treatment arm and surgical outcome. Secondary outcomes were the surgeon's judgment of completeness of procedure, menstrual blood loss, uterine fibroid related and general quality of life, pain, recovery, hospitalization, complications, and surgical reinterventions. Follow-up period was 1 year. The risk difference between both treatment arms was estimated, and a Farrington-Manning test was used to determine the p-value for noninferiority (noninferiority margin 7.5% of incomplete resections). Data were analyzed according to the intention-to-treat principle, including a per-protocol analysis for the primary outcome. A total of 209 women participated in the study and underwent hysteroscopic myomectomy with PSA (n = 106) or GA (n = 103). Mean age was 45.1 [SD 6.4] years in the PSA group versus 45.0 [7.7] years in the GA group. For 98/106 women in the PSA group and 89/103 women in the GA group, data were available for analysis of the primary outcome. Hysteroscopic resection was complete in 86/98 women (87.8%) in the PSA group and 79/89 women (88.8%) in the GA group (risk difference -1.01%; 95% confidence interval (CI) -10.36 to 8.34; noninferiority, P = 0.09). No serious anesthesiologic complications occurred, and conversion from PSA to GA was not required. During the follow-up period, 15 serious adverse events occurred (overnight admissions). All were unrelated to the intervention studied. Main limitations were the choice of primary outcome and the fact that our study proved to be underpowered. Conclusions Noninferiority of PSA for completeness of resection was not shown, though there were no significant differences in clinical outcomes and quality of life. In this study, hysteroscopic myomectomy for type 0 and 1 fibroids with PSA compared to GA was safe and led to shorter hospitalization. These results can be used for counseling patients by gynecologists and anesthesiologists. Based on these findings, we suggest that hysteroscopic myomectomies can be performed under PSA in an outpatient setting. Trial registration The study was registered prospectively in the Dutch Trial Register (NTR 5357; registration date: 11 August 2015; Date of initial participant enrollment: 18 February 2016).